La fabrique de l'intégration - Di Donato, Flora (Regards anthropologiques, 2020)
The debate on the integration of foreigners regularly returns to the heart of Swiss news. The concept of "successful integration" is particularly central in the context of naturalization, a long and complex procedure, sometimes surprisingly unfolding. The result of scientific research carried out on the basis of concrete cases by five specialists in social sciences and law, this book explores the meaning of the concept of integration as a criterion allowing access to nationality, from the point of view of authorities as well as that of persons applying for naturalization. And we can see that the expression "The Swiss makers" (Les faiseurs de Suisses", "Die Schweizermacher"), put forward by the famous film directed by Rolf Lyssy, in 1978, which one believed to belong to the past, remains relevant.